ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL - Badri, Rico Elhando (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2022)
The capital structure balances external (long-term) capital with internal capital. This research aims to find out the effect of liquidity, uniqueness and profitability on the capital structure of food and beverage subsector companies listed on the Indonesia Stock Exchange from 2014 to 2018. The research sample used consisted of 7 companies listed on the Indonseia Stock Exchange, sampling targets set certain standards for 5 years, and the amount of data of 35 companies. Data analysis methods use multiple regressions. The results of this study show that liquidity variables affect the structure of capital. This is because liquid companies tend to use relatively small amounts of debt for their working capital and can meet their financing needs, but unique variables affect the capital structure. The uniqueness of the company's products leads to high costs, so more capital is used and fluctuating profitability does not affect the capital structure. The decline in sales led to a decrease in the company's sales